LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR IN OTOUTHES RUBER (SCHNEIDER, 1801) FROM THE GULF OF MANNAR AND PALK BAY - Jayasankar, P (Indian Journal of Fisheries, 2011)
The regression coefficients of length-weight relationship in females and males O. ruber showed no significant difference and a common regression is recommended. The regression coefficients depart significantly from 3. Total length-relative condition factor curve showed first major inflexion at 200 mm